Moderation of the effects of discrimination-induced affective responses on health outcomes. Issue 2 (1st February 2018) - Gerrard, Meg; Gibbons, Frederick X.; Fleischli, Mary E.; Cutrona, Carolyn E.; Stock, Michelle L.
Abstract : Objective: The goal of the study was to examine differential mediation of long-term effects of discrimination on health behaviour and health status by internalising (anxiety and depression) and externalising (hostility and anger), and to explore moderation of these effects, specifically, by the presence of support networks and coping tendencies. Design: The current analyses employed structural equation modelling of five waves of data from Black female participants of the Family and Community Health Study over 11 years ( M age 37–48). Main Outcomes Measures: The main outcome variables were health status and alcohol use (frequency and problematic consumption). Results: Perceived racial discrimination was associated with increases in internalising and externalising. In addition, internalising reactions to discrimination were associated with deterioration in health status and increases in problematic drinking; externalising reactions were associated with increases in frequency of drinking. These relations were attenuated by availability of support networks, and exacerbated by use of avoidance coping. Conclusion: The current study (a) replicated previous research suggesting that two different types of affective reactions mediate the relations between perceived racial discrimination and physical health status vs. health-impairing behaviours: internalising and externalising, and (b) revealed moderation of these effects by coping mechanisms.